Ecology and Economy of Home Gardens in a Village Environment of the Brahmaputra Valley, Assam - Deka, Nityananda; Bhagabati, A.K. (National Geographical Journal of India, 2022)
The home gardens in the human habitats of the Brahmaputra floodplain constitute some unique production units maintained traditionally by the rural communities. With the shrinkage of the natural forest areas and consequent biodiversity loss, the importance of these gardens as repositories of local bioresources has substantially increased. This paper makes an attempt to study the status of and changes in the character of the home gardens and their ecological and economic roles in the context of a village located in the Brahmaputra floodplain, Assam. The study is based on primary data collected from the households, field visits and interviews with the family heads and mapping of the layout of the gardens and plant species available in them